Sokongan dan halangan yang dihadapi pelajar-pelajar kurang upaya di sebuah institusi pengajian tinggi di Malaysia - Hasnah Toran,; Mohd Hanafi Mohd Yasin,; Mohd Mokhtar Tahar,; Norasuzaini Sujak Abstrak Kajian, (Penerbit Universiti Kebangsaan Malaysia, 2009)
This research was carried out to identify supports received and barriers faced by students with disabilities in an institute of higher education in Malaysia. Respondents for this research were students with vision impairment, two students with hearing impairment, and six students with physical impairment. Data from students with hearing and physical impairment were collected in written form while data from students with vision impairment were collected through interviews. Among the issues brought up by these students were inaccessible physical infrastructures on campus, lack of sign language interpreters for students with hearing impairment, lack of computers accessible for people with vision impairment, assistance in the library, accessible transportation system, issues of bureaucracy, and lack of empathy from the campus community. In terms of support, respondents reported that they depended on close friends to assist them; to follow lectures for students with hearing impairment and to move from one place to another for students with vision impairment. To improve the quality of service and facilities for students with disabilities in institutes of higher education in Malaysia, among the suggestions put forward by these respondents were to increase the awareness of issues faced by students with disabilities among the campus community and improve their understanding, to set up a council that could communicate their needs to the university administrators in taking steps towards a more positive physical and social environment on campus in order to provide an equal opportunity for these students to achieve their optimal potential